1994
DOI: 10.1108/09684899410071699
|View full text |Cite
|
Sign up to set email alerts
|

Employee Empowerment

Abstract: Explains the development of employee empowerment from its beginnings as American academic research to its successful adaptation by the Japanese management and later US management. In its present state employee empowerment or participation flourishes in many different methods of management and takes many different forms in its practice. Examines contingent factors affecting implementation of participative management practices and points out the various dilemmas to avoid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…Looking at evidence from US 'new economy' firms, Sesil et al (2002) found that those with stock option schemes tended to perform better. These mixed results may, in part, reflect the extent to which the fact of owning shares is far removed from the experience of day-to-day work and gains appear relatively arbitrary (see Nykodym et al, 1994). As Bakan et al (2004) note, share ownership plans and similar forms of financial participation can be rather complicated, making understanding of their operation difficult for employees with limited formal education.…”
Section: The Differing Motives Types and Effects Of Financial Particmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking at evidence from US 'new economy' firms, Sesil et al (2002) found that those with stock option schemes tended to perform better. These mixed results may, in part, reflect the extent to which the fact of owning shares is far removed from the experience of day-to-day work and gains appear relatively arbitrary (see Nykodym et al, 1994). As Bakan et al (2004) note, share ownership plans and similar forms of financial participation can be rather complicated, making understanding of their operation difficult for employees with limited formal education.…”
Section: The Differing Motives Types and Effects Of Financial Particmentioning
confidence: 99%
“…Studies conducted in a wide range of contexts provide mixed results regarding performance outcomes (D'Art and Turner, 2004;Nykodym et al, 1994;see also McNabb and Whitfield, 1998). Blasi et al (1996) found no clear relation, although the balance tended towards more favourable results from employee stock ownership plans (ESOPs), especially in the case of smaller firms.…”
Section: The Differing Motives Types and Effects Of Financial Particmentioning
confidence: 99%
“…To ensure managers were responsive to their employees, performance reviews of managers included employee development, 360 degree appraisal, and managers' achievements through delegation and the use of man-management skills. Employee participation may happen in the form of employees taking part in decisions and making their own individual contribution, employees working together with management, or employees collaborating with coworkers in project or work groups (Nykodym et al, 1994). The next section reviews the literature on empowerment in the context of empowerment implementation with the purpose of gaining knowledge of ways to put empowerment theory into practice effectively in general and more specifically through the use of teams.…”
Section: Simmons (1995)mentioning
confidence: 99%
“…Morley (1995) explored the concept of empowerment and raises questions about the possible reason for its rise to dominance as a current discourse in the United Kingdom public services. Nykodym et al (1994) investigated the development of employee empowerment from its beginnings as American academic research to its successful adaptation by the Japanese management and later US management.…”
Section: Introductionmentioning
confidence: 99%